Production of silicon carbide reinforced molybdenum disilicide composites using high-pressure sintering. Issue 15 (15th October 2020) - Guan, Shixue; Liang, Hao; Liu, Yang; Lin, Weitong; He, Duanwei; Peng, Fang
Abstract: Studying the mechanical and thermal properties as well as the relationship between microstructure evolution and strengthening mechanisms is crucial for obtaining superior high-temperature refractory molybdenum disilicide-silicon carbide composites. In this study, molybdenum disilicide and silicon carbide powders with different volume ratios were used to fabricate molybdenum disilicide-silicon carbide composites via high pressure and high temperature at 5.5 GPa/1773 K. The introduction of the second phase improved the materials' mechanical properties. Transmission electron microscopy demonstrated that severe plastic deformation generated numerous micro-defects and grain refinement during the high pressure sintering process. The second phase enhancement also improved the samples' performances. Under high pressure and high temperature sintering process, the thermal and mechanical properties of the materials increased dramatically, including a well Vickers hardness ( 20.6 GPa), fracture toughness ( 10.3 MPa·m 1/2 ) and thermal stability (>1673 K).